PENGARUH KONSENTRASI Na2S TERHADAP KEKUATAN TARIK DAN KEMULURAN PADA KULIT ULAR AIR (Hemalopsis Buccata) - Elis Nurbalia (Politeknik ATK Yogyakarta, 2016)
The purpose of this study was to determine the effect of the concentration of Na2S in the process liming/ scaling the tensile strength and elongation water snake crust leather (Hemalopsis Buccata). Raw material used is 12 sheets of water snake skin (Hemalopsis Buccata). In the scales removing process Na2S was used with concentration level of 0.5 oBe; 0.75 oBe; 1.0 oBe; 1.25 oBe. At the end of the crust leather tanning process, tensile strength and elongation were tested. The test results will be compared with SNI No. 06-4586-1998 of the quality requirements of chrome tanned water snake finished leather. From the tensile strength test result, increased concentrations of Na2S resulted in decreased tensile strength, though it still in accordance with the SNI with requirement at least 1000 N / cm2. From the elongation test results, note that all the elongation above a maximum of 30% requisite by SNI. Nonetheless refers to the suitability of common data quality requirements of various types of finished leather from BASF (2004), the leather still can be processed leather products due to the strong and soft texture. Increasing concentrations of Na2S will increase the pH value at the liming/ scaling and influence the tensile strength.